Comparative Analysis Of The Effect Of Sawdust And Coal Combustion On Fouling Formation - M Dimas Maulana I; Royb Fatkhur Rizal (CV. AFDIFAL MAJU BERKAH, 2026)
The utilization of biomass in the form of sawdust as a co-firing fuel in boilers has increasingly been implemented to reduce coal consumption and carbon emissions. Sawdust has a high volatile matter content and is readily available; however, its ash characteristics, which contain alkali elements such as potassium (K) and sodium (Na), as well as its relatively low ash melting point, have the potential to increase fouling formation on boiler heat transfer surfaces. Fouling refers to the accumulation of deposits on the economizer, superheater, reheater, and air preheater, which can reduce heat transfer efficiency, increase flue gas temperature and differential pressure (DP), increase induced draft fan load, decrease main steam temperature, and increase sootblower operating frequency. This study aims to analyze the effect of sawdust combustion on fouling formation using boiler operational data obtained from the Distributed Control System (DCS). The parameters analyzed include coal flow rate, sawdust flow rate, total fuel flow, co-firing percentage, primary air flow, secondary air flow, flue gas O₂ content, furnace exit gas temperature (FEGT), flue gas temperature to the stack, economizer differential pressure, air preheater differential pressure, main steam temperature, and sootblower operating frequency. Data were collected at fuel mixture variations of approximately ±3% sawdust relative to the total fuel flow, with hourly intervals for a minimum of 24 hours for each operating condition. The analysis was conducted by comparing changes in temperature, differential pressure, and boiler performance at each variation of sawdust percentage. Indications of increased fouling were identified by rising flue gas temperatures and differential pressure, reduced heat transfer effectiveness, and increased sootblower operation requirements. The results of this study are expected to show that increasing the percentage of sawdust tends to increase fouling formation; however, there is still an optimum limit for sawdust utilization that can be applied without significantly reducing boiler efficiency and reliability.